Gender inequality and cardiovascular diseases - S. H. Lilothia (Российский кардиологический журнал)
Despite generally accepted recognition of the difference in characteristics and outcomes of cardiovascular diseases between men and women, implementation of a gender and sex-specific approach for the treatment of women in clinical practice has been extremely slow or non-existent. Women continue to be hospitalized at later stages of the disease, receive less aggressive medical care, often experience recurrent symptoms of the disease, and have a lower quality of life. Furthermore, sex biased research and significant knowledge gaps still persist. Meanwhile, women's cardiovascular health requires not only sex-specific research, but also an acknowledgement of the complex interaction of gender and sociocultural aspects that influence women's lives and cardiovascular outcomes. Developing sex and gender-specific algorithms for timely diagnosis, risk stratification, follow-up, and referral for surgical intervention, incorporating sex and gender into research, and studying the mechanisms of differences may help reduce the gap in outcomes between women and men. The aim of the article is to provide a framework of current barriers for cardiac female patients and to equip physicians with information about potential solutions. This article covers terminology and relevant aspects of the subject of cardiovascular inequalities, history of inclusion of women in clinical trials, women's mortality rates for cardiac surgery, and tips on managing the problem.